PENGARUH PENAMBAHAN LIMBAH SERBUK KAYU DAN ZAT ADITIF NANO3 TERHADAP KUAT TEKAN DAN TARIK BELAH BETON - Ritonga, Achmad Munir; Khairul Muslim; Silitonga, Frangky (PPM Sdirjianbang Akademi Militer, 2023)
Waste wood dust in handling still takes a lot of special attention, so that the waste does not pollute the environment. One attempt to utilize the waste sawdust, wood shavings author will mix into the concrete mix. NaNO3 accelerator additives are added to this mixture to help the process of hardening of the concrete. In making specimens using materials include gresik cement, sand from Merapi, gravel, water, sawdust, and additives NaNO3. The tools used for testing concrete is compression machine, the tool is used in the testing of concrete compressive strength test and tensile test concrete sides. From the test results generated value for the average compressive strength of concrete at 3 days with 0%, 3%, 5% respectively sawdust is 9.71 MPa, 3.68 MPa, 1.60 MPa. For the average compressive strength of the concrete life of 7 days with 0%, 3%, 5% respectively sawdust is 12.92 MPa, 6:12 MPa, 3.67 MPa while the average compressive strength of concrete age of 28 consecutive days was 24.90 MPa , 15:37 MPa, 9:52 MPa. For the average value Pull apart the concrete test cube 28 days with sawdust levels of 0%, 3%, 5% is 2.79 MPa, 0.72 MPa, 0:10 MPa. So from these data it is concluded that concrete with a mixture of 3% sawdust can be categorized as a lightweight concrete because it has a specific gravity of less than or equal to 2200 kg / cm 3 and can be used as a non-structural concrete as it has f'c> 15 MPa.